Utilization of Plastic Waste as Planting Media in Efforts to Handle Inorganic Waste - Arshy Prodyanatasari; Jerhi Wahyu Fernanda (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
Plastic waste is one of the wastes generated from human activities and is classified as inorganic waste. Inorganic waste is difficult or cannot be decomposed, especially if the plastic is made of non-biodegradable materials. The increase in plastic waste is one of the problems faced by all parties and can threaten environmental sustainability. Efforts that can be made to minimize plastic waste are to recycle plastic waste into valuable products, such as planting media. The purpose of this community service activity is to manage plastic waste into planting media. This aims to minimize environmental pollution due to plastic waste, especially plastics that are classified as non-biodegradable. The methods used in this activity are lectures and demonstrations. The activity was attended by 37 people consisting of village officials, PKK mothers, and Karang Taurna of Blimbing Village, Kediri Regency. In this PKM activity, the participants seemed enthusiastic about participating in a series of activities from waste management education and also demonstrations in making planting media. In this activity, it is known that there is an increase in participants' knowledge about good waste management. As a follow-up effort, similar and relevant activities are needed so that public knowledge and awareness of the importance of good and correct waste management will increase, so as to create a healthy and sustainable environment.